The risk of social media addiction between the ideal/false and true self: Testing a path model through the tripartite person-centered perspective of authenticity. (December 2021) - Monacis, L.; Griffiths, M.D.; Limone, P.; Sinatra, M.
Highlights: There are direct and indirect paths from self-alienation to risk for social media addiction. There is an indirect path from accepting external influence to risk for social media addiction. There is an indirect path from authenticity to a lower risk of becoming addicted to social media. Selfitis behaviors help in understanding individual's self-presentation on social media. Abstract: Much previous research has focused on the important role played by personality constructs in developing addictive use of social media. However, no investigation has yet been conducted examining the association between dispositional authenticity and online self-idealization, or the authentic self-expression hypothesis and the risk of becoming addicted to social media. To fill this gap, the present study tested a path model that hypothesized direct and indirect effects of the three components of authentic personality on social media addiction via selfitis behaviors. Participants (N = 490; Mage = 20.31 years, SD = 3.76) recruited from high schools and universities completed a self-report survey assessing the three authentic personality traits, selfitis behaviors, and social media addiction. Results generally confirmed the supposed pathways. Direct and indirect effects on social media addiction were discussed by integrating the two mechanisms of compensation related to individual dispositions with the online self-idealizing and authentic self-expression hypothesis underlying selfitis behaviors. Whereas self-alienation was found to have positive direct and indirect effects on increasing of the likelihood of becoming addicted to social media, both traits of the tendency to accept external influence and authenticity showed indirect effects in opposite directions on the risk of addictive use of social media. Findings from the present study extend previous research by exploring inter-individual differences in predisposing and reinforcing factors associated with the online self-presentation.